Elaboración de una guía metodológica para la alineación, formulación y evaluación de proyectos de inversión privada (2015)
In this paper documenting a methodological guide that includes the processes identified for alignment, development and financial evaluation of private investment projects, aiming to provide an option for companies or organizations who wish to undertake a project, it was done without regardless of their magnitude. Is a brief description of its contents, along with the overall process, the table of breakdown of activities, general concepts, techniques, tools and results that facilitate understanding and application in each of the chapters. In the first chapter, the proposed macro alignment process, formulation and financial evaluation of projects, continuing the approach chapter of the idea as the main source for the emergence of projects presented. Once you have defined the project concept, development of identification and strategic alignment is proposed, which, it is proposed to analyze the environment and the economic sector that allows the designer to devise a strategy aligned to the organization that will develop the project or the economic sector when it comes to an entrepreneurial idea in order to obtain approval to proceed with the project formulation stage. After the alignment of the project, in Chapter 4, the formulation of the project is proposed, in which indicated how they should be developed market studies, technical, environmental, and administrative costs and profits, so the designer You can make selection of alternatives and finally, ensure the financial assessment to determine the feasibility of the project at the pre-feasibility or feasibility.